2020
DOI: 10.1016/j.heliyon.2020.e05420
|View full text |Cite
|
Sign up to set email alerts
|

n–polynomial exponential type p–convex function with some related inequalities and their applications

Abstract: In this paper, the idea and its algebraic properties of n –polynomial exponential type p –convex function have been investigated. Authors prove new trapezium type inequality for this new class of functions. We also obtain some refinements of the trapezium type inequality for functions whose first derivative in absolute value at certain power are n –polynomial exponential type p –convex. At the end, some new bounds for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Awan et al [11] keeping his work on generalizations, introduced a new class called n-polynomial harmonically convex function. Motivated and inspired by the ongoing activities and research in the convex analysis field, we found out that there exists a special class of function known as exponential convex function, and nowadays, a lot of people working are in this field [12,13]. Dragomir [14] introduced the class of exponential type convexity.…”
Section: Introductionmentioning
confidence: 99%
“…Awan et al [11] keeping his work on generalizations, introduced a new class called n-polynomial harmonically convex function. Motivated and inspired by the ongoing activities and research in the convex analysis field, we found out that there exists a special class of function known as exponential convex function, and nowadays, a lot of people working are in this field [12,13]. Dragomir [14] introduced the class of exponential type convexity.…”
Section: Introductionmentioning
confidence: 99%
“…Tariq, a young mathematician along with his collaborators used the property of convexity and Hypergeometric functions to define some new definitions and inequalities such as exponentially s-type convexity, generalised exponentially convexity and p-harmonic exponential type convexity (see [13][14][15][16][17][18]). Many mathematicians have applied this inequality for fractional estimates of Hermite-Hadamard inequalities using different kinds of convexity (see, for example, [19][20][21][22][23][24][25][26]).…”
Section: Introductionmentioning
confidence: 99%
“…They have also explained that due to the strong relationship between them, while working on any one of the concepts it can be applied to the other one as well. Convexity theory has gained a lot of attention in recent years and many generalizations and refinements of convexity analysis for inequalities have been found (see, for example [9][10][11][12][13][14][15]).…”
Section: Introductionmentioning
confidence: 99%